PERANCANGAN SISTEM PEMESANAN ONLINE JASA PRINT OUT BERBASIS ANDROID MENGGUNAKAN METODE SCRUM - Joko Susilo (Institut Bisnis dan Informatika Kwik Kian Gie, 2021)
The technology itself will continue to be updated by looking at the current level of people's lives. From technological developments in the world of informatics from time to time continues to progress very rapidly making all government agencies, as well as education want to develop and use technological sophistication that is able to improve various kinds of performance. At present the progress of information technology is very needed in accessing information quickly, and has become a major need in information services to provide the system needed in a timely and accurate manner. The Android-based print out service ordering application is used by users to make it easier to place orders directly through a smartphone by relying on an Android application. Ordering process in the form of analysis using UML. Keyword: Android, Information System, Print Out.